FEATURES OF THE GEOGRAPHICAL DISTRIBUTION OF TERRESTRIAL MOLLUSCS IN THE CAUCASUS - M. Z. Magomedova (Юг России: экология, развитие)
Aim. High population, high proliferation rates, a large species diversity, low mobility and small ability to overcome geographic barriers, ease of collecting material and sensitive response to changes in the external environment makes this group a convenient object of biogeographic and ecological research. Methods. The inventory of Caucasian ground malacofauna made it possible to make a complete list of species; their characteristics were determined by the geographical distribution of major natural regions of the Caucasus. Results. The comparative analysis of the geographical distribution of terrestrial molluscs on key areas of the Caucasus showed that among the 352 species belonging to 140 genera of 36 families, most richly represented Western Caucasus, which accounts for 51% or 181 species from 80 genera of 20 families, while the share of Armenian, Eastern and Central Caucasus accounts for 35-37%. Talysh, in turn, is characterized by the presence of only 11% of the species composition of the Caucasian land mollusc. Caucasus limited in distribution among the analyzed species is 72% or 255 species belonging to 104 genera of 24 families. Conclusion. The results prove the species diversity of the different regions of theCaucasus and could serve as the basis to reconsider the possible ways of formation of fauna of the region discussed.